2013
DOI: 10.1186/1471-2458-13-696
|View full text |Cite
|
Sign up to set email alerts
|

HPV and cervical cancer related knowledge, awareness and testing behaviors in a community sample of female sex workers in China

Abstract: BackgroundLimited data suggested that the prevalence of Human Papillomavirus (HPV) among female sex workers (FSW) is much higher than in the general female population. The current study aimed to examine the HPV and cervical cancer related awareness, knowledge, and behaviors among FSW in China.MethodsA total of 360 FSW recruited from entertainment establishments in Beijing completed a self-administered survey including demographics, HPV related knowledge, and health-seeking and cervical cancer preventive behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
43
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 36 publications
11
43
1
Order By: Relevance
“…Likely, it was discovered that HPV and the beginning of the sexual experience at an early age increases the risk of cervical cancer in a study similar to ours conducted in China 24 .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Likely, it was discovered that HPV and the beginning of the sexual experience at an early age increases the risk of cervical cancer in a study similar to ours conducted in China 24 .…”
Section: Discussionsupporting
confidence: 55%
“…In our study, 56.3% and 53.4% of FSWs reported having heard of HPV and HPV vaccination, respectively. In a study conducted on FSWs in China, the rates of knowing HPV and HPV vaccination was lower than our study (22.1%, 13.3%) 24 . On the other hand half of FSWs were aware of the consequences of HPV infection in a study performed in Thailand 25 .…”
Section: Discussionmentioning
confidence: 52%
“…Hence, extensive health education about cervical cancer to create awareness to the public is needed which could be channelled through health facility-based talks as well as mass media including the local FM radios. 8 Cervical cancer prevention campaigns should be conducted which should include husbands and local community leaders because they are essential in motivating women to participate in cervical screening programmes. 8 This study has some limitations and measurement bias.…”
Section: Discussionmentioning
confidence: 99%
“…34 Even among sex workers -women who are the highest risk for HPV infection -despite the majority (71%) had heard of cervical cancer, only 22% had ever heard of HPV and 13.3% had ever heard of HPV vaccine, with presumably even less knowing the linkage between HPV and cervical cancer. 35 Among MSM less than 1 in 5 (18.3%) were willing to pay for HPV vaccine given its high price and just more than a third (34.9%) would be willing to disclose their sexuality to a doctor in order to get HPV vaccine, even if it was free of charge to MSM. Our figure on the acceptance of HPV vaccine among MSM was lower than that in a recently published systematic review on data from various countries (36-74%).…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies showed that the median age of first sex was 20 years among MSM 38 and 19 among MNSM. 35 HPV vaccine was recommended to be taken before sex debut. This was the reason we chose the age of 20 years among MSM and 19 among MNSM as cut-off age in comparing the willingness to take free vaccine.…”
Section: Discussionmentioning
confidence: 99%